Taurine and Oxidative Stress in HIV - Burini, Roberto C. [UNESP] (2018)
Taurine (Tau) (2-aminoethanesulfonic acid) is an amino acid, lacking the carboxyl group and messenger ribonucleic acid. As a major intracellular free amino acid, Tau regulates the osmolality and cell membranes stabilization. Moreover, due to its ability to generate conjugates with bile acids, xenobiotics, retinoic acid, and chloramine, Tau is involved in a diverse array of physiological functions, including detoxification, osmoregulation, membrane stabilization, calcium modulation, neurotransmitter agonist, antioxidation, and immunomodulation. As antioxidant Tau scavenges the phagocyte microbicidal agent HOCl to form the more stable and less toxic taurine chloramine (Tau-Cl) therefore acting as cytoprotectant, in the attenuation of apoptosis. As antiinflammatory agent Tau-Cl suppresses superoxide anion and decreases both NO and proinflammatory cytokines secretion by the activated phagocytes, body Tau comes from diet or from its endogenous biosynthesis from methionine (Met) and cysteine (Cys). Tau occurs naturally in food, especially in seafood and meat. The main organs involved in Tau metabolism are the gut, liver, and kidneys. Usually, plasma Tau levels decrease in response to surgical injury, trauma, sepsis, and cancer. In our data with HIV+ patients the low plasma Tau followed the other thiol-antioxidant pattern. Cys supplementation and methionine loading in HIV+ resulted in higher production of glutathione (GSH) and Tau than non-HIV+ controls. Tau normalization was obtained by methionine loading and was found associatively to similar transmethylation and remethylation of Met and lower transsulfuration of homocysteine compared with controls. Thus, the increased flux of Cys into GSH and Tau pathways seems to be a host strategy to strengthen the cellular antioxidant capacity against the HIV progression.